Antimicrobial activity of zno nanoparticles: synthesis using Artocarpus Gomezianus fruit mediated facile green combustion method - R. ANITHA; K.V. RAMESH (International Journal of Pharma and Bio Sciences, 2017)
Zinc Oxide nanoparticles have been proven to be competent antibacterial and antifungal activity for medical applications because of their strong redox ability, nontoxicity, long-term stability and low cost. Spherical ZnO nanoparticles were synthesized by eco-friendly green combustion method using citrate containing Artocarpus gomezianus fruit extract as a fuel. Prepared ZnO nanoparticles exhibit significant antibactericidal activity against Bacillus cereus, Escherichia coli, Serratia marcescens and antifungal activity against Malassezia furfur using the zone of inhibition method. The study successfully demonstrates synthesis of spherical ZnO nanoparticles by simple eco-friendly green combustion method exhibit antimicrobial activities. Further, this method can effectively need for the preparations of ZnO for the medical applications in controlling pathogenic bacteria with better dispersion and consequently, better efficiency in food and textiles industry.